RELEVANSI DOKTRIN WORK MADE FOR HIRE DALAM KARYA KECERDASAN BUATAN: TINJAUAN HUKUM HAK CIPTA INDONESIA - Rayhan Surya Gemilang; Emilda Kuspraningrum; Setiyo Utomo (Universitas Labuhanbatu, 2025)
The rapid development of artificial intelligence (AI) has raised various legal issues, particularly regarding the determination of copyright ownership of works produced with the assistance or intervention of AI systems. In the context of Indonesian law, there are currently no specific regulations governing the legal status of AI-based works, resulting in a legal vacuum in the copyright regime. Based on the principle of the rule of law as stipulated in the 1945 Constitution of the Republic of Indonesia, the state has the authority to formulate regulations to ensure legal certainty and protection in the field of intellectual property. This study aims to analyze the regulation of artificial intelligence from a copyright law perspective through a comparative approach to regulations in several countries and to examine the relevance of applying the work made for hire doctrine as a normative solution in Indonesian law. The research method used is doctrinal legal research with a legislative and comparative law approach. The results of the study show that several countries, such as the United States, the United Kingdom, and China, have developed regulatory frameworks or specific legal doctrines to address copyright issues over AI-based works. In contrast, Indonesia still does not have specific regulations that accommodate these developments. Therefore, this study recommends the need to update Law Number 28 of 2014 concerning Copyright by integrating provisions regarding artificial intelligence, one of which is through the limited adoption of the work made for hire doctrine, in order to provide legal certainty and copyright protection that is adaptive to technological developments.Keywords: work made for hire; copyright law; artificial intelligence; legal reform; intellectual property